PEMBIAYAAN MUDHARABAH DAN DAMPAKNYA TERHADAP OMSET USAHA MIKRO DI KOPERASI SIMPAN PINJAM PEMBIAYAAN SYARIAH EL-UMMA - TAMI NADIRAH; DENI LUBIS; ALLA ASMARA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
Micro Enterprise Sector is a sector that has an important  role in the economy of the country. However the number of problems still felt by the sector, one of them  is the problem of capital. Mudharabah  ﬁnancing can be an alternative for micro businesses to resolve the problem. KSPPS El-Umma  is one of the institution  that oﬀer Mudharabah  ﬁnancing for micro business actors in developing their business. This study aims to analyze the eﬀectiveness of mudharabah ﬁnancing and its impact on business turnover.  The method that used in this research is descriptive analysis method  using Likert  scale to measure  the eﬀectiveness level of ﬁnancing disbursed and to describe the impact of ﬁnancing  on business development  also using Ordinary  Least Square (OLS) method to determine the factors that inﬂuence the business turnover. The result of analysis with Likert scale as a whole mudharabah ﬁnancing distributed by KSPPS has been classiﬁed as eﬀective, and there is business development  after getting ﬁnancing  seen from the increase of business turnover.  The Factors that inﬂuencing the turnover of business are the length of business, age, the amount  of ﬁnancing  and the term of ﬁnancing.